2020
DOI: 10.14720/aas.2020.115.2.1411
|View full text |Cite
|
Sign up to set email alerts
|

Correlation and path coefficient analysis among agro-morphological and biochemical traits of okra [Abelmoschus esculentus (L.) Moench] genotypes in Ethiopia

Abstract: <p><em></em>Thirty six okra genotypes were evaluated for different agro-morphological and biochemical traits at Melkassa Agricultural Research Center, Ethiopia during 2018 main season using 6 x 6 simple lattice design. The objectives were to assess the correlation of agro-morphological and biochemical traits with fruit yield and to partition the correlation in to direct and indirect effects through path analysis. The genotypic correlation was positive and significant for fruit yield per hecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…The positive correlation between okra pod yield and okra morphological characteristics, such as plant height, number of leaves, leaf area, stem girth, number of nodes and plant weight, agrees with the findings of Mahmoud et al (2020) that good vegetative growth is necessary to attain high okra yield. However, the positive and negligible effect of plant height on okra pod yield in this study corroborates Mohammed et al (2020) who reported the same.…”
Section: Discussionsupporting
confidence: 91%
“…The positive correlation between okra pod yield and okra morphological characteristics, such as plant height, number of leaves, leaf area, stem girth, number of nodes and plant weight, agrees with the findings of Mahmoud et al (2020) that good vegetative growth is necessary to attain high okra yield. However, the positive and negligible effect of plant height on okra pod yield in this study corroborates Mohammed et al (2020) who reported the same.…”
Section: Discussionsupporting
confidence: 91%